The alarmin S100A9 hampers osteoclast differentiation from human circulating precursors by reducing the expression of RANK. Issue 9 (14th June 2019) - Di Ceglie, Irene; Blom, Arjen B.; Davar, Robab; Logie, Colin; Martens, Joost H. A.; Habibi, Ehsan; Böttcher, Lisa‐Marie; Roth, Johannes; Vogl, Thomas; Goodyear, Carl S.; van der Kraan, Peter M.; van Lent, Peter L.; et al.
ABSTRACT: The alarmin S100A8/A9 is implicated in sterile inflammation‐induced bone resorption and has been shown to increase the bone‐resorptive capacity of mature osteoclasts. Here, we investigated the effects of S100A9 on osteoclast differentiation from human CD14 + circulating precursors. Hereto, human CD14 + monocytes were isolated and differentiated toward osteoclasts with M‐CSF and receptor activator of NF‐κB (RANK) ligand (RANKL) in the presence or absence of S100A9. Tartrate‐resistant acid phosphatase staining showed that exposure to S100A9 during monocyte‐to‐osteoclast differentiation strongly decreased the numbers of multinucleated osteoclasts. This was underlined by a decreased resorption of a hydroxyapatite‐like coating. The thus differentiated cells showed a high mRNA and protein production of proinflammatory factors after 16 h of exposure. In contrast, at d 4, the cells showed a decreased production of the osteoclast‐promoting protein TNF‐α. Interestingly, S100A9 exposure during the first 16 h of culture only was sufficient to reduce osteoclastogenesis. Using fluorescently labeled RANKL, we showed that, within this time frame, S100A9 inhibited the M‐CSF‐mediated induction of RANK. Chromatin immunoprecipitation showed that this was associated with changes in various histone marks at the epigenetic level. This S100A9‐induced reduction in RANK was in part recovered by blocking TNF‐α but not IL‐1. Together, our data show that S100A9 impedes monocyte‐to‐osteoclast differentiation, probably via a reduction in RANK expression.—Di Ceglie, I., Blom, A. B., Davar, R., Logie, C., Martens, J. H. A., Habibi, E., Böttcher, L.‐M., Roth, J., Vogl, T., Goodyear, C. S., van der Kraan, P. M., van Lent, P. L., van den Bosch, M. H. The alarmin S100A9 hampers osteoclast differentiation from human circulating precursors by reducing the expression of RANK. FASEB J. 33, 10104–10115 (2019). www.fasebj.org